Answer:
[tex]x=32768.000[/tex]
Step-by-step explanation:
One is given the following expression:
[tex]log_2(x)+log_4(x)=5[/tex]
Use the logarithm base change rule, which states the following:
[tex]log_b(y)=\frac{log(y)}{log(b)}[/tex]
Remember, a logarithm with not base indicated is another way of writing a logarithm to the base of (10). One can apply the base change rule to this situation:
[tex]log_2(x)+log_4(x)=5[/tex]
[tex]\frac{log(x)}{log(2)}+\frac{log(x)}{log(4)}=5[/tex]
Factor out (log(x)),
[tex](log(x))(\frac{1}{log(2)}+\frac{1}{log(4)})=5[/tex]
Inverse operations:
[tex]log(x)=\frac{5}{\frac{1}{(log(2)+log(4)}}[/tex]
Simplify,
[tex]log(x)=5(log(2)+log(4))[/tex]
[tex]log(x)=4.51545[/tex]
Now rewrite the logarithm, remember, a logarithm is another way of writing an exponent, in the following format:
[tex]b^x=y\ \ -> log_b(y)=x[/tex]
[tex]log(x)=4.51545[/tex]
[tex]10^4^.^5^1^5^4^5=x[/tex]
[tex]32768.000=x[/tex]